Essential, Overlapping and Redundant Roles of the Drosophila Protein Phosphatase 1α and 1β Genes - Kirchner, Jasmin (Copyright © 2007 by the Genetics Society of America, 2007)
Protein serine/threonine phosphatase type 1 (PP1) has been found in all eukaryotes examined to date and is involved in the regulation of many cellular functions, including glycogen metabolism, muscle contraction, and mitosis. In Drosophila, four genes code for the catalytic subunit of PP1 (PP1c), three of which belong to the PP1α subtype. PP1β9C (flapwing) encodes the fourth PP1c gene and has a specific and nonredundant function as a nonmuscle myosin phosphatase. PP1α87B is the major form and contributes ∼80% of the total PP1 activity. We describe the first mutant alleles of PP1α96A and show that PP1α96A is not an essential gene, but seems to have a function in the regulation of nonmuscle myosin. We show that overexpression of the PP1α isozymes does not rescue semilethal PP1β9C mutants, whereas overexpression of either PP1α96A or PP1β9C does rescue a lethal PP1α87B mutant combination, showing that the lethality is due to a quantitative reduction in the level of PP1c. Overexpression of PP1β9C does not rescue a PP1α87B, PP1α96A double mutant, suggesting an essential PP1α-specific function in Drosophila.